Meta-analyses of the effects of high-intensity interval training in elite athletes — part II: relationships between the mean effects on various performance measures - Wiesinger, H. P.; Hopkins, W. G.; Haller, N.; Blumkaitis, J.; Strepp, T.; Stöggl, T. L. (Frontiers in Physiology, 2024)
Introduction: Our recent meta-analyses have demonstrated that high-intensity interval training (HIIT) causes a range of mean changes in various measures and predictors of endurance and sprint performance in athletes. Here, we extend the analyses to relationships between mean changes of these measures and consider implications for understanding and improving HIIT that were not apparent in the previous analyses.